The Influence of Thyroid Function, Inflammation, and Obesity on Risk Prediction of Acute Kidney Injury by Cystatin C in the Emergency Department - Moritz Schanz; Dirk Pannes; Jürgen Dippon; Christoph Wasser; Mark Dominik Alscher; Martin Kimmel (Karger Publishers, 2016)
Background/Aims: There is a growing role for emergency departments (ED) in assessing acute kidney injury (AKI) for hospital admissions but there are few studies addressing acute kidney injury biomarkers and confounding factors in the ED. Cystatin C (CysC), a newer renal biomarker, is influenced by thyroid function, inflammation and obesity. This study aims to be the first study to address the impact of these parameters in the ED. Methods: Admitted patients (n=397) were enrolled in the ED at Robert-Bosch-Hospital, Stuttgart, Germany. Daily serum creatinine (sCr) was recorded for AKI classification by Kidney Diseases Improves Global Outcome (KDIGO) criteria. CysC, thyroid stimulating hormone (TSH), thyroxine (T4), C-reactive protein (CRP) and body mass index (BMI) were registered at enrollment in the ED. Serum samples were collected at enrollment, after 6 hours and in the following mornings (day 1 to day 3). The correlation of CysC and sCr was studied on a two variable logistic regression model. A linear predictor was computed to predict minimal AKI stage and area under the curve (AUC) was calculated. Results: Of 397 patients enrolled for classification by KDIGO AKI criteria, n=152 (38%) developed AKI, n=69 (17.4%) reached AKI stage I, n=70 (17.6%) AKI stage II, and n=13 (3%) AKI stage III. Although a correlation between CRP and CysC levels was shown (rho=0.376), this didn't affect the predictive ability for AKI according to our data. We compared receiver operating characteristic (ROC) curves (DeLong test) of CysC to ROC curves of CysC with the additional variables TSH, BMI, and CRP respectively. Our data shows that addition of CRP, TSH, or BMI does not improve prediction of AKI stage beyond prediction based solely on CysC levels. Conclusions: CysC is known to be influenced by thyroid function, inflammation and obesity, but in our large ED population there was no significant impact of these factors on the diagnostic accuracy of CysC to detect AKI in ED patients.